Meningkatkan kinerja pemerintah daerah dengan transparansi dan akuntabilitas - Adyaksana, Rahandhika Ivan; Alqurani, Lutfi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2020)
This research aims to determine the effect of accountability and transparency on the performance of local governments. The method used in this research is quantitative. The data used was primary data and obtained by visiting the location directly (field research) and providing a research questionnaire to the respondent. The research population was consisted of employees working in SKPD of Bantul Regency. Total population is 29 SKPD in Bantul Regency. The sample selection method uses purposive sampling technique. Total sample is 86 respondents were obtained by distributing questionnaires in 2019. Data were analyzed using multiple linear regression. The variables in this study are Accountability (X1), Transparency (X2) and Government Performance (Y). The results of the study prove that accountability and transparency have a significant and positive effect on government performance